The effect of bupivacaine on the proliferation and metastasis of tumor cells in an in vitro model of perineural invasion of cholangiocarcinoma and its mechanism - CHEN Menshou, FENG Yujie (精准医学杂志)
Objective To investigate the effect of bupivacaine on the proliferation and metastasis of tumor cells in an in vitro model of perineural invasion of cholangiocarcinoma and its mechanism. Methods Human cholangiocarcinoma cell line (QBC939 cells) were divided into QBC939 group (group A), QBC939+well-differentiated pheochromocytoma cell line (PC12) group (group B), and QBC939+PC12+bupivacaine group (group C). The cells in group A were cultured in the QBC939 cell-specific medium for 48 h, those in group B were co-cultured with well-differentiated PC12 cells for 48 h in addition to the treatment in group A to establish the in vitro model of perineural invasion of cholangiocarcinoma, and those in group C were cultured with bupivacaine for 48 h in addition to the treatment in group B. CCK-8 assay, EDU staining, cell scratch assay, and Transwell assay were used to measure cell viability and assess the proliferation, migration, and invasion abilities of the three groups of cells. Well-diffe-rentiated PC12 cells were divided into PC12 group (group D) and PC12+bupivacaine group (group E), and the cells in group D were cultured in the PC12 cell-specific medium for 48 h, while those in group E were cultured with bupivacaine for 48 h in addition to the treatment in group D. Immunofluorescence staining assay was used to measure the length of cell axons, and Western blotting was used to measure the relative expression level of neuropilin-1 (NRP-1) in the two groups. Results CCK-8 assay, EDU staining, cell scratch assay, and Transwell assay showed that compared with B, group C had significantly lower cell viability and proliferation, migration, and invasion abilities of QBC939 cells (F=34.39-149.20,q=9.47-12.95,P<0.05). Immunofluorescent staining and Western blotting showed that compared with group D, group E had a significantly shorter mean length of cell axons and a significantly lower relative protein expression level of NRP-1 (t=11.75,3.09,P<0.05). Conclusion Bupivacaine may inhibit the malignant biological behaviors of cholangiocarcinoma cells such as proliferation, migration, and invasion by inhibiting the axonal growth of neural cells and the expression of NRP-1 in an in vitro model of perineural invasion of cholangiocarcinoma.